FROM NEEDS ANALYSIS TO DESIGNING ACADEMIC WRITING MATERIALS FOR DIPLOMA STUDENTS OF MARA UNIVERSITY OF TECHNOLOGY (UITM), MALAYSIA - Noemi, Nancy Chiuh @ (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
When students begin their undergraduate studies, they will need to adjust to the demands of the undergraduate studies with regard to academic English at university level. Dudley-Evans & St. John (1998, p.37) maintain that âtheir English tuition up to the tertiary level will generally have been in the area of General English, and is unlikely to have included specific preparation for study at university levelâ¦â Barker (2000, p.8), in his study on first year studentsâ perception of writing difficulties, found that the students âcome to realise during first semester that they are not adequately prepared for the writing demands required at universityâ. Pecorari (as cited in Phakiti & Li, 2011) found that Asian ESL students had problems in academic writing; âthe students begin their aca-demic writing from âcopyingâ which implies a lack of training in academic writing and arouses accusations of plagiarism in their writingâ (p.232). Being an English-medium public university in Malaysia, MARA University of Technology (UiTM) poses challenges to both its students and instructors, as a good command of English is essential. In its attempt to equip its undergraduate students with language skills, UiTM has introduced credit-bearing English courses. This paper presents the findings from a research project to identify the academic writing needs of first-year Diploma in Public Administration students in UiTM Sabah. A total of 110 Diploma in Public Administration students and six instructors responded to the questionnaires. The research examined the studentsâ and instructorsâ perceptions of the importance of academic writing skills the students need in order to complete their undergraduate programmes, assessment of the studentsâ academic writing skills, and the difficulty of academic writing skills. The findings indicated that there was consistency of response between the students and instructors. The follow-up interviews and focus groups with instructors and students confirmed this. The findings from the needs analysis are then used as the basis for developing academic writing materials to complement the existing English courses in UiTM.